All-Inside Single-Bundle Reconstruction of the Anterior Cruciate Ligament with the Anterior Half of the Peroneus Longus Tendon Compared to the Semitendinosus Tendon: A Two-Year Follow-Up Study - Bi, Mingguang; Zhao, Chen; Zhang, Shuijun; Yao, Bin; Hong, Zheping; Bi, Qing (The Journal of Knee Surgery, 2018)
The anterior half of the peroneus longus tendon (AHPLT) has been reported to be acceptable for ligament reconstruction with respect to strength and safety. However, there is little information regarding the clinical outcomes after using the AHPLT compared with other autograft tendons. A prospective randomized controlled study was performed to compare the results of 62 cases of all-inside anatomical single-bundle anterior cruciate ligament (ACL) reconstruction using the AHPLT and 62 cases using semitendinosus graft with an average of 30.0 ± 3.6 months' follow-up. Tunnel placements of enrolled cases were measured on three-dimensional (3D) computed tomography (CT) and X-ray imaging. Knee stability was assessed using the anterior drawer test, pivot shift test, and KT-1000. The International Knee Documentation Committee (IKDC) 2000 subjective score was used to evaluate functional outcomes. The American Orthopedic Foot and Ankle Score (AOFAS) and the assessment of eversion muscle strength were performed to evaluate the function of the ankle donor site. Tunnel positions, which were confirmed with 3D CT, were in the anatomical positions. At the final follow-up, there were no significant differences between the semitendinosus group and the AHPLT group in the IKDC score (90.4 ± 7.1 vs. 89.3. ± 8.4), KT 1000 measurements (1.71 ± 0.57 vs. 1.85 ± 0.77), pivot shift test, and Visual Analogue Scale (VAS) (0.15 ± 0.36 vs. 0.10 ± 0.30). No obvious ankle site complications were found at 24 months. The average AOFAS score of the AHPLT group was comparable to that of the semitendinosus tendon group (99.1 ± 1.40 vs. 99.5 ± 1.21). There was no significant difference in clinical outcomes or knee stability between the semitendinosus group and the AHPLT group at the 2-year follow-up. An AHPLT autograft may be a good alternative for all-inside ACL reconstruction with respect to its strength, safety, and donor site morbidity.
Keywords: anterior cruciate ligament; all-inside; peroneus longus tendon; donor site